Prospects for steam coal exporters in the era of climate policies: a case study of Colombia - Pao-Yu Oei; Roman Mendelevitch (Climate Policy, 2019)
Continued global action on climate change has major consequences for fossil fuel markets, especially for coal as the most carbon-intensive fuel. This article summarizes current market developments in the most important coal-producing and coal-consuming countries, resulting in a critical qualitative assessment of prospects for future coal exports. Colombia, as the world's fourth largest exporter, is strongly affected by these global trends, with more than 90% of its production being exported. Market analysis finds Colombia in a strong competitive position, owing to its low production costs and high coal quality. Nevertheless, market trends and enhanced climate policies suggest a gloomy outlook for future exports. Increasing competition on the Atlantic as well as Pacific market will keep coal prices low and continue pressure on mining companies. Increasing numbers of filed bankruptcies and lay-offs might be just the beginning of a carbon bubble devaluing fossil fuel investments and leaving them stranded. Colombia largely supplies European and Mediterranean consumers but also delivers some quantities to the US Gulf Coast, and to Central and South America. Future coal demand in most of these countries will continue to decline in the next decades. Newly constructed power plants in emerging economies (India, China) are unlikely to compensate for this downturn owing to increasing domestic supply and decreasing demand. Therefore, maintaining or even increasing mining volumes in Colombia should be re-evaluated, taking into account new economic realities as well as local externalities. Ignoring these risks could lead to additional stranded investments, aggravating the local resource curse and hampering sustainable economic development. Key policy insights: The climate policies of most of Colombia's traditional trade partners target steam coal as the more emission-intensive fossil fuel, with many countries implementing or considering a coal phase-out. Coal exporters should re-evaluate their operations and new investments taking into account this new policy environment. To prevent a race to the bottom among coal producers that would favour weak regulation, climate policy makers should also consider the local social and external costs of coal mining, including on health and the local environment.
Keywords: 330; Case study; Climate policy; Colombia; Decarbonization; Energy policy; Steam coal market